Taxonomia de algas fossilíferas cretáceas da formação Santana, em rochas ornamentais no município de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The Araripe Basin, located in northeastern Brazil, has abundant wealth in relation to its fossil records. The Cariri Stone, has numerous records of fossil organisms, among them, the important in this work, the abundant algae fragmentation, in its visual aspect. For these and other aspects, their rocks are mined and sold as an end product for ornamental rocks. In the municipality of Santarém -PA, this type of rocks appears as cladding rocks in walls, sidewalks, pool edges, among others. In the face of the study, four distinct points of covering rocks were found that have numerous algae fragments. Samples of ornamental rocks were collected in marble for macro analysis and micro visualization in the laboratory, resulting in the taxonomic identification of fossil algae such as Codium Genus and Oedeogonium Genus, derived from lagoon environment, Santana formation.
Keywords: Formação Santana; Membro Crato; Algas fósseis; Santarém – Pa; CNPQ:: CIÊNCIAS BIOLÓGICAS